Analisis Peran Public Relation terhadap Strategi Marketing Bank Syariah Indonesia (BSI) - ALMUZAYYAD, ALMUZAYYAD (Maliki Interdisciplinary Journal, 2025)
This study aims to analyze the role of Public Relations (PR) in the marketing strategy of Bank Syariah Indonesia (BSI), the largest Islamic bank in Indonesia. In the banking industry, the role of PR is very important in maintaining reputation and building a positive image in the eyes of the public, especially in introducing the concept of inclusive Islamic banking. The method used in this study is qualitative with a literature study and observation approach. The results of the study show that PR plays a strategic role in supporting BSI's marketing through digital campaigns, marketing events, and corporate social responsibility (CSR) activities. PR also plays an important role in crisis management, maintaining good relations with the media, and building a narrative that strengthens BSI's image as a transparent and ethical bank. In conclusion, the synergy between PR and marketing strategies is effective in expanding market reach and increasing customer loyalty.